Pengaruh Arus Kas Operasi, Ukuran Perusahaan, Dan Leverage Terhadap Kualitas Laba Pada Perusahaan Manufaktur Di Bursa Efek Indonesia - Lea Amanda; Muhammad A H; Oriadi Oriadi; Rosadi F; Sugiyanto Sugiyanto (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to examine the effect of operating cash flow, company size, and leverage on earnings quality in manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the period 2020 to 2024. The method used is an associative quantitative approach using secondary data from annual financial reports. A total of 80 observation samples were obtained after applying data completeness criteria over five years of observation (2019–2023). Based on a series of econometric tests, the Fixed Effect Model (FEM) was determined to be the most appropriate estimation model for panel data regression analysis. The hypothesis testing results showed statistically significant findings, both partially and simultaneously. Simultaneously, the combination of Operating Cash Flow, Company Size, and Leverage was found to significantly affect Earnings Quality (p-value < 0.05). Further partial testing confirmed that the three independent variables individually had a significant effect on Earnings Quality (p-value = 0.001). These findings overall reinforce Agency Theory and Signaling Theory, concluding that internal company factors, such as liquidity (cash flow) and capital structure (leverage), play an important role in determining the credibility of the financial statements presented.